Oncoplastic breast conservation surgery is oncologically safe when compared to wide local excision and mastectomy. (April 2017) - Mansell, J.; Weiler-Mithoff, E.; Stallard, S.; Doughty, J.C.; Mallon, E.; Romics, L.
Abstract: Background: Support for the oncological safety of oncoplastic breast conservation surgery (OBCS) is mostly based on evidence comparing recurrence rates after OBCS to wide local excision (WLE). However, OBCS is often indicated for larger cancers and oncological results should also be compared to patients treated with mastectomy. In this study we compared recurrence and survival following OBCS, mastectomy and WLE. Methods: Patients treated with OBCS between 2009 and 2012 were identified from a prospectively maintained database. For comparison, consecutive patients treated with WLE or mastectomy with or without immediate reconstruction (Ms ± IR) over the same time period were identified. Histological variables of patients were compared using Fisher Exact or Chi squared tests, and recurrence and survival were compared using Kaplan-Meier and Cox regression survival analysis. Results: 980 patients' data were analysed (OBCS: n = 104; WLE: n = 558; Ms ± IR: n = 318). Tumour size, grade, nodal status, ER, and PR expression of patients treated with OBCS were all significantly more adverse compared with patients treated with WLE (p < 0.001). These histological variables were similar in patients treated with Ms ± IR and OBCS. 5-year local recurrence rates were similar in all three groups (WLE: 3.4 per cent, OBCS: 2 per cent, Ms ± IR: 2.6 per cent; log rank = 0.973), while distant recurrence rates were higher after Ms ± IR and OBCS (Ms ± IR:13.1 per cent, OBCS:7.5 per cent, WLE:3.3 per cent; log rank: p < 0.001). Conclusion: OBCS is oncologically safe in patients even when histological results are similar to patients treated with Ms ± IR. Highlights: Pathology results after oncoplastic breast conservation are similar to mastectomy, but significantly different from WLE. Local recurrence rate after oncoplastic breast conservation is similar to wide local excision and mastectomy. Disease free and cancer specific survival after oncoplastic conservation is comparable to mastectomy. Oncoplastic breast conservation is oncologically safe even when tumour pathology is similar to mastectomy.